Design principle, 4E analyses and optimization for onboard CCS system under EEDI framework: A case study of an LNG-fueled bulk carrier - Tian, Zhen; Zhou, Yihang; Zhang, Yuan; Gao, Wenzhong (Energy (Oxford), 2024)
With the accelerated implementation of Energy Efficiency Design Index (EEDI) phase 3 by the International Maritime Organization, shipping carbon reduction is urgently required. This paper explores the possibility to develop the onboard carbon capture and storage (OCCS) system unstraints between EEDI phases 3 and 4. The OCCS is particularly established with the utilization of exhaust gas waste heat and LNG cold energy. The proposed OCCS system is modelled in Aspen HYSYS, laying the foundation for energy, exder the EEDI framework. The OCCS system design principle for an LNG-fueled bulk carrier is determined with the conergy, economic and environment analyses. Furthermore, the multi-objective optimization is based on the energy and exergy efficiency of OCCS system (ηen,OCCS × ηen,OCCS), payback period (PBP) and metric of carbon capture efficiency degree (MCCED) by non-dominated sorting genetic algorithm-Ⅲ. The Pareto frontier indicates that the system is in optimal operation with the exhaust gas mass flow rate of 29,990 kg/h and the liquid-to-gas ratio of 1.04. The carbon capture is 1048.0 kg/h, which is 70.74% over EEDI phase 3 requirements. The optimized ηen,OCCS × ηen,OCCS is 2.92%, the PBP is 13.03 years and the MCCED is 23.00%. This study provides an important basis for the maritime post-combustion carbon reduction compliance. •Design principle of the onboard CCS system is established under the EEDI framework.•Balance between waste heat and LNG cold energy is achieved with the OCCS system.•The CO2 gap for the reference ship to satisfy EEDI phase 3–4 is 613.8–1114.3 kg/h.•The optimized overall system energy and exergy efficiencies are 29.20% and 10.01%.•The PBP for the OCCS system is 13.03 years under the optimal working conditions.